Integrasi Nilai Islam Moderat dalam Pendidikan Islam untuk Menguatkan Harmoni Sosial Keagamaan pada Masyarakat Plural - Ramadhan, Mochammad Rizal (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
This paper explains about how the integration of moderate Islamic values ​​in Islamic education which in this era is a major challenge that must be faced by plural society. To strengthen social and religious harmony, it is needed integration of Islamic values, especially moderate Islam, is said to be important because with the integration of moderate Islamic values ​​in Islamic education, people will be able to interact well with one another. Socio-religious harmony that needs to be strengthened, because with a strong socio-religious harmony in a plural society, the harmony of life between religious communities, mutual tolerance, and mutual affection between communities will be achieved and survive in a plural society at large. Keywords: Value Integration, moderate Islam, social harmony, plural society